Antibiotic sensitivity of some bacteria isolates isolated from scouring calves from some farms in Oyo and Ogun States, Nigeria (2018)
Diarrhoea in young pre-weaned calves is one of the most important causes of calf morbidity and mortality. Information on this multi-aetiological condition is scanty in Nigeria. Therefore, we studied the prevalent bacteria and antibacteria susceptibility to various bacterial isolates from faecal samples of suspected cases of calf scours in Oyo and Ogun States of South-western Nigeria. One hundred and twenty calf faecal samples (120) from various breeds of cattle showing clinical manifestation of scours were screened for bacterial agents in two farms in Oyo and five farms in Ogun States. Isolation and identification were done using standard procedures, while antibiotic sensitivity was done using Kirby Bauer's disc diffusion method. Escherichia coli, Salmonella spp. and Campylobacter spp. were identified. Out of all the calves, 19 calves (15.8%) were positive for bacteria agents, E. coli was isolated from 12 calves (10%), Salmonella spp. was isolated in 10 calves (8.3%) and Campylobacter spp. was isolated in 1 calf (0.8%). Antibiotic sensitivity test revealed that the most sensitive antibiotics were Meropenem (91.3%) and Amikacin (82.6%) while the least sensitive was Ampicillin (21.7%). Therefore Meropenem is the most sensitive antibiotic and recorded the highest percentage sensitivity in all the three bacteria pathogens isolated, while Ampicillin appeared to be the least sensitive antibiotic to virtually all the pathogens isolated. Meropenem is therefore recommended as the drug of choice for the management of bacteria calf scours. The isolation of highly pathogenic E.coli 0157 from calf scour cases reaffirmed cattle as a reservoirs host which may enter the food chain and poses a faeco-oral potential public health hazards.